PENGGUNAAN TULISAN DALAM AKAD NIKAH TUNA WICARA PERSPEKTIF MASYARAKAT BANJAR DAN WAHBAH AZ-ZUHAILI - Hafidzi, Anwar; Whulansari, Sisca (Universitas Islam Negeri Alauddin Makassar, 2024)
This study discusses the priority between writing and gestures in the marriage contract of individuals with speech impairments. In practice, sometimes the use of writing is prioritized, but there are also those who prefer gestures. The purpose of this research is to understand how the Banjar community views the priority of using writing in the marriage vow for individuals with speech impairments, and how Wahbah Az-Zuhaili's perspective in Kitab Fiqh al-Islami wa Adillatuhu relates to the priority of using writing in the marriage vow for individuals with speech impairments.This is an empirical legal study, where data is collected through interviews and literature review. The findings of the study show that some members of the Banjar community prioritize gestures because they are considered more practical, while others choose writing due to concerns that gestures may not be clearly understood. Despite the differences in opinion, there is consensus that the marriage is still valid as long as the conditions and pillars of the marriage contract are fulfilled. Meanwhile, in Kitab Fiqh al-Islami wa Adillatuhu, Wahbah Az-Zuhaili states that writing is prioritized in matters of divorce (thalaq) and declaration (iqrar) because it holds the same level of importance as a clear (sharih) statement. However, using or prioritizing gestures is also acceptable, and the marriage remains valid as long as the conditions and pillars of the marriage contract are met.